Indian Perspective of Burnout Among Plastic Surgeons - Ankur Karanjkar; Nikhil Panse; Smita Panse; Parag Sahasrabudhe (Indian Journal of Plastic Surgery)
Introduction Over the last decade, the term “Burnout” has become familiar term in all walks of life, particularly medicine. Emotional exhaustion, depersonalization, and a low sense of personal accomplishment make up the triad. At least a third of plastic surgeons are having burnout according to the western literature. Data on burnout in Indian plastic surgeons is lacking. We have made an attempt to analyze the incidence and factors responsible for burnout among plastic surgeons in India. Materials and Methods An online survey was conducted in India to assess burnout among plastic surgeons from June to November 2019. Consent, demographic information, stress-related factors, the abbreviated Maslach Burnout Inventory (aMBI), and Satisfaction with Medicine were all included section wise in the survey. Both used scales were validated. Data were gathered using Google forms, then uploaded to an Excel file and analyzed. A multivariable and univariable analysis of factors associated with burnout was carried out. Results Twenty-two percent of 330 plastic surgeons who responded were assessed to have moderate to high emotional exhaustion, 5% had moderate to high depersonalization, and 3% had low personal accomplishment. The overall burnout rate was 8.2%. Seventy-three percent of plastic surgeons enjoyed a good to very good quality of life. Great over-volume of work, mid-career practicing plastic surgeons and professional satisfaction with work were found to have a significant association with burnout on multivariate analysis. Conclusions Plastic surgeons in India suffer an overall burnout rate of 8.2% with a multifactorial etiology. This occupational hazard is preventable and reversible. Plastic surgeons need to be vigilant about this and seek help whenever required.